2001
DOI: 10.1097/00002480-200105000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of Cryopreserved Arterial Allografts: Comparison with Fresh and Glutaraldehyde Treated Grafts

Abstract: The use of cryopreserved aortic allografts in cardiovascular surgery is widespread and has resulted in excellent outcomes. However, it is controversial whether cryopreservation suppresses the antigenicity of tissue. We designed experimental models to study whether the cryopreservation process alters antigenicity in comparison with that found in fresh and glutaraldehyde treated tissues. Fresh, cryopreserved, and glutaraldehyde treated thoracic aorta from Brown Norway rats were subcutaneously implanted into Lewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…They blamed allograft failures on immune rejection possibly due to retained antigenicity after cryopreservation (8). Moriyama and colleagues also compared inflammatory infiltrates after heterotopic transplantation of fresh and cryopreserved arterial allografts to gauge any suppression of antigenicity through cryopreservation, reaching a negative conclusion (9). Using rats to assess the effects of cryopreservation on heart valve and vascular allografts, Saito et al similarly discovered that cell viability was sustained and allograft antigenicity was unaltered during cryopreservation (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They blamed allograft failures on immune rejection possibly due to retained antigenicity after cryopreservation (8). Moriyama and colleagues also compared inflammatory infiltrates after heterotopic transplantation of fresh and cryopreserved arterial allografts to gauge any suppression of antigenicity through cryopreservation, reaching a negative conclusion (9). Using rats to assess the effects of cryopreservation on heart valve and vascular allografts, Saito et al similarly discovered that cell viability was sustained and allograft antigenicity was unaltered during cryopreservation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although some data suggest a decline in allograft antigenicity by doing so, thus raising hopes of immunosuppressant-free transplantation (and eliminating side effects, costs) (5-7), there is also evidence to the contrary (8)(9)(10)(11). Yokomise and colleagues successfully conducted tracheal allotransplantation in dogs, without use of immunosuppressants, by immersing grafts in a cryopreservative solution and deep freezing (−85 ℃) for 285±28 days (~8-10 months) (12).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response might lead to replacement by a tracheal structure with mucociliary epithelium and newly formed cartilage [10]. Both fresh and cryopreserved allograft vascular tissues induce a potent cellular and humoral immune response in recipients [17][18][19]. Also, an inflammatory response to an aortic allograft is especially profound in younger age groups [20].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of antigenicity of the vascular allograft plays a role in the process of biodegradation. Recent immunological studies have shown that venous allografts, cold-stored as well as cryopreserved, are antigenic and that the antigenicity is not modified by cryopreservation [19,20] . Tissue matching and immunosuppressive therapy are important issues in vascular transplantation.…”
Section: Discussionmentioning
confidence: 99%